Systemic immune-inflammatory complex index as a novel predictor of sepsis prognosis: a retrospective cohort study using MIMIC-IV - Wang, Xueqing; Lin, Yingxin; Zhang, Sheng; Wang, Junshi; Huang, Bin; Luo, Hua; Huang, Lei (Frontiers in Medicine, 2025)
PurposeSepsis is a life-threatening condition with high mortality and morbidity, making its early detection is critical. Current diagnosis relies on the Sequential [sepsis-related] Organ Failure Assessment score, which is complex and time-consuming to determine. Herein, we proposed a novel index, the systemic immune-inflammatory complex index (SIICI), defined as (neutrophil × monocyte count) × 103/(platelet × lymphocyte count), to predict illness severity, and we verified its prognostic value.MethodsAll data were extracted from the Medical Information Mart for Intensive Care database IV (MIMIC-IV). Cox proportional hazards and Kaplan–Meier survival analyses were used to determine the association between target indices and 30- and 90-days mortality. Restricted cubic splines were used to reveal the linear relationship between indices and mortality. To assess the prognostic value of the SIICI, the systemic immune-inflammation index (SII) and systemic inflammation response index (SIRI), the area under the receiver operating characteristic curve (AUC), and the Youden index were measured and compared. Propensity score matching was used to reveal the association between the SIICI and secondary outcomes. Finally, subgroup analysis was performed to confirm the predictive ability of the SIICI.ResultsWe included 3,944 patients; among these, 609 (15.4%) and 663 (16.8%) patients had 30- and 90-days mortality, respectively. Our findings showed a strong association between the SIICI and mortality at 30 and 90 days in all models, which was more pronounced and better stratified than for the SIRI and SII. The p-value was < 0.05 in all cases; however, the SIICI was closer to a linear relationship with mortality than the SIRI or SII. Additionally, the SIICI had a higher AUC and Youden value than the other two indices. Moreover, a higher SIICI was positively associated with a longer stay in the intensive care unit or the hospital, an increased incidence of acute kidney injury, and greater use of renal replacement therapy and mechanical ventilation.ConclusionThe SIICI was positively associated with sepsis mortality and showed a better prognostic value than the SIRI and SII. The SIICI may be a promising complementary index to classical scoring systems for early assessment of patients with sepsis.